LANGUAGE CHANGE AND MODES OF THINKING THE LOSS OF INFLEXIONS IN OLD ENGLISH - Jesus, Martinez del Castillo (European Scientific Journal, ESJ, 2015)
Language is the creation of meanings. A language is a technique for any kind of speech, functioning in a particular speech community. As a technique of speaking it is constituted by a set of forms, contents, rules, procedures, attitudes and a system of beliefs ruling in the so-called a state of the language, that is, the analogous language ruling in a period of time. Since human subjects, that is, speakers, have the peculiar condition of beingtogether- with-others, the manifestation of this condition of humans, a language, is nothing but a historical object. Because of this, languages, as the manifestation of human intelligence and freedom in a speech community, will change in history, because all speakers participate in the construction and reconstruction of it. The way every language changes is something to be explained internally in the speech community. My thesis is that the changes known as the loss of inflexions were prompted with the introduction of a new way of thinking. The way of thinking, for the Anglo-Saxons in Old English, was a dynamic way of conceiving of things. Things were considered events happening. With the contacts of Anglo-Saxons with Celtic-Roman people, first, the introduction of Christianity, second, and finally with the Norman invasion, their dynamic way of thinking was confronted with the static conception of things coming from the Mediterranean. The history of English up to the 15th century meant the confrontation of two mental conceptions, static vs. dynamic.